MANAGEMENT PHYSIOTHERAPY FOR BELL'S PALSY DEXTRA WITH CHEMOTHERAPY TUMOR'S NEUROENDOKRIN ON CAVUM NASI IN RSUD KRMT WONGSONEGORO SEMARANG: A CASE STUDY - Wibisono, Yhusuf (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Physiotherapy for Bell's Palsy Dextra with chemotherapy Tumors Neuroendocrine on cavum nasi. Implementation of therapy with modalities infra- red , massage and Propiceptif Neuro Facilitation / PNF face. Case Presentation: To report the results of a program of physiotherapy on the bell's palsy dextra with chemotherapy tumors of neuroendocrine on cavum nasi. The patient was a woman aged 57 years with a primary diagnosis of Bell's palsy Dextra the moment is undergoing chemotherapy for tumors of neuroendocrine on cavum nasi . Physiotherapy was done as much as 12 times the detail infra- red on the face side of the right for 10 minutes , massage performed for 5 minutes , exercise with techniques Propioceptif Neuro Facilitation / PNF. Implementation of therapy 2 times a week . Management and Outcome: Having done 12 times therapeutic obtained results occurs increase the value that is measured by the scale of Ugo Fisch from 0 becomes 18 Discussion: therapy for 1.5 months is still with a score scale ugo fisch 18, while the evidence of clinical improvement occurs in spontaneously in a time of three weeks in 85 percent of cases , and most great people eventually recover the function of the face are normal Conclusion: In case this does not happen an increase in the significant value of the Scale Ugo Fisch . It is the possibility because the patient still undergo chemotherapy so that the immune patients disturbed.